The service quality provided by invest Melaka Berhad in promoting Melaka as an investment destination towards customer satisfaction / Azwina Shafira Romli - Romli, Azwina Shafira (Faculty of Business and Management, 2007)
The good quality in delivering service is very important towards customer satisfaction nowadays. Therefore, it is important for the company to focus on how to improve customer satisfaction with study what is the service quality element that will influences customer satisfaction itself. This research is about a study on relationship between factors influencing customer satisfaction focus on promoting Melaka as an investment destination by Invest Melaka Berhad. The element of service quality such as responsiveness, reliability, assurance, tangible and empathy have been identified in order to investigate whether or not these factors have significant relationship with customer satisfaction. The survey is conducted at Ayer Keroh, Melaka. The sample size for this study is 80 customers who are also have experience in using Invest Melaka Berhad services. Data obtained using primary and data. Respondents are required to answer the questionnaires that include the statements regarding factors influencing customer satisfaction. Once the necessary data has been collected, the data will be analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 14.0 has been used to summarize the data. The results are in the form of reliability testing, frequency, and correlation. Based on this research, the result indicates that there are significant relationship between all the factors which include responsiveness, reliability, assurance, tangible and empathy toward customer satisfaction. This finding focuses on whether the effective service quality is really impact on customers to become satisfaction towards Invest Melaka Berhad. From the analysis, the result shows that there is significant relationship between service quality and customer satisfaction.